2022
DOI: 10.1021/acsomega.2c01236
|View full text |Cite
|
Sign up to set email alerts
|

IRMPD Spectroscopy of Bare Monodeprotonated Genistein, an Antioxidant Flavonoid

Abstract: Genistein is a naturally occurring polyphenol belonging to the family of flavonoids with estrogenic properties and proven antioxidant, anti-inflammatory, and hormonal effects. Genistein and its derivatives are involved in radical scavenging activity by way of mechanisms based on sequential proton-loss electron transfer. In view of this role, a detailed structural characterization of its bare deprotonated form, [geni-H] − , generated by electrospray ionization, has been performed by tande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
(121 reference statements)
1
2
0
Order By: Relevance
“…Comparison of the calculated spectra with the experimental one of [Nar + H] + , reported in Figures 3 and S11 In general, for all conformers considered, the 180°rotation of C4′−OH has little influence on relative energies, yielding species with similar free energy as observed for neutral naringenin. 20 Furthermore, in agreement with similar findings in an IRMPD study on deprotonated genistein 68 and with an IR study on neutral naringenin, 69 the calculated IR spectra for each pair of such conformers are completely superimposable as can be noted in the calculated spectra IR collected in the Supporting Information (Figures S10−S12).…”
Section: Irmpd and Computational Study Comparison Of Irmpd Spectra Fo...supporting
confidence: 86%
“…Comparison of the calculated spectra with the experimental one of [Nar + H] + , reported in Figures 3 and S11 In general, for all conformers considered, the 180°rotation of C4′−OH has little influence on relative energies, yielding species with similar free energy as observed for neutral naringenin. 20 Furthermore, in agreement with similar findings in an IRMPD study on deprotonated genistein 68 and with an IR study on neutral naringenin, 69 the calculated IR spectra for each pair of such conformers are completely superimposable as can be noted in the calculated spectra IR collected in the Supporting Information (Figures S10−S12).…”
Section: Irmpd and Computational Study Comparison Of Irmpd Spectra Fo...supporting
confidence: 86%
“…As their deprotonated ions, the pair of isomers has only two exchangeable hydrogens (Figure ). Notably, these two compounds also have known deprotonation sites from previous work, allowing for confident identification of the H/D exchange sites. These two isomers were resolved after 3 m of cIMS-MS separation (Figure , left). When subjected to our HDX-induced mass-distribution-based shift analysis, it was found that despite only having two labile hydrogens exchanged for deuteriums, their t Rel.…”
Section: Resultsmentioning
confidence: 86%
“…80,81 Interestingly, as compared to our previous work, we observed orthogonality between these HDX-induced mass-distributionbased shifts and the arrival time order of the isomers, themselves. We attribute this orthogonality to be based on how the mass distribution of each molecule changes upon deuteration, where upon doubling the mass of an atom from H to 2 H, its contribution to the center of mass and moment of inertia is increased as compared other atom mass changes (e.g., 35 Cl to 37 Cl or 79 Br to 81 Br). Lastly, we demonstrated inverse isotopologue shifts for 4-iodoaniline, which we attribute to the change in mass distribution, and specifically center of mass contributions, between the d0 and d3 isotopologues.…”
Section: ■ Conclusionmentioning
confidence: 99%